2018
DOI: 10.1111/pcn.12682
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of brexpiprazole for the treatment of acute schizophrenia in Japan: A 6‐week, randomized, double‐blind, placebo‐controlled study

Abstract: Brexpiprazole was efficacious and well tolerated in Japanese adult patients with acute SCZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 14 publications
0
50
0
1
Order By: Relevance
“…Recently, a DBRCT of brexpiprazole for patients with acute schizophrenia as a Phase II/III study was conducted in Japan. 7 Surprisingly, this study found that brexpiprazole 2 mg/day, but not 4 mg/day, was superior to placebo for improvements in the PANSS total score and that neither brexpiprazole 4 nor 2 mg/day were superior to placebo for improvements in the PANSS positive subscale score and response rate. 7 On the basis of these findings, brexpiprazole 4 mg/day was not approved in Japan for the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Recently, a DBRCT of brexpiprazole for patients with acute schizophrenia as a Phase II/III study was conducted in Japan. 7 Surprisingly, this study found that brexpiprazole 2 mg/day, but not 4 mg/day, was superior to placebo for improvements in the PANSS total score and that neither brexpiprazole 4 nor 2 mg/day were superior to placebo for improvements in the PANSS positive subscale score and response rate. 7 On the basis of these findings, brexpiprazole 4 mg/day was not approved in Japan for the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 57%
“…We did not retrieve any additional studies from the clinical trial registries ( Figure S1 ). Finally, three DBRCTs 4 , 5 , 7 were selected for inclusion. The total numbers of patients in the various arms were as follows: brexpiprazole 4 mg/day: n=477; brexpiprazole 2 mg/day: n=483; and placebo: n=484.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various antipsychotics have been approved for schizophrenia treatment in Japan; however, the only antipsychotic medications for which there have been 6-week, double-blind, randomized, placebo-controlled trials as phase 3 trials in Japan are asenapine (ASE) [17], BLO-P [14], brexpiprazole (BRE) [18], and paliperidone extended-release (PAL-ER) [19]. All of these were included in the review.…”
Section: Introductionmentioning
confidence: 99%